Journalism Yesterday, Today and Tomorrow. Interview with Andrej Tušer - Tušer, Andrej; Hudíková, Zora (Communication Today, 2018)
The interview presents Professor Andrej Tušer’s opinions on various topics related to journalistic genres and issues modern journalism has to face, with emphasis on the press. Particular attention is paid to addressing the opportunities for independent journalism and the freedom of expression in the current socio-political situation, as well as to the impact of journalism on politicians and their behaviour. His perspectives on the rapidly changing conditions within journalism, contemporary methods of media production, competences of journalists in the age of multi-platform journalism and the development of the Internet and online journalism are also included. Professor Tušer’s practical experience and theoretical expertise are reflected in a range of concepts concerning theoretical issues of journalistic production – including the meaning of genres in contemporary journalism and the position of regional and local print media. The given responses function as thorough, important and critical reflections of this patriarch of Slovak print journalism and journalism theory on the development and the current state of discursive journalism issues in connection with dynamic socio-political and technological transformations.